2022
DOI: 10.1016/j.cub.2021.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Measuring biodiversity from DNA in the air

Abstract: In briefEnvironmental (e)DNA is shed by all species and can be collected to monitor biodiversity-revolutionizing research, particularly in aquatic ecosystems. Clare et al. collect vertebrate eDNA from the air to identify terrestrial diversity and predation. Airborne eDNA was recovered hundreds of meters from sources, indicating that populations may be monitored at a distance, significantly advancing terrestrial ecology.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
93
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 42 publications
4
93
2
Order By: Relevance
“…The 49 detected species included zoo animals, locally occurring animals, and animals used as feed at the zoo. The ability to detect this range of vertebrates through airborne eDNA is supported by Clare et al 19 We found an increased probability of detecting airborne eDNA from animals present in high biomass and within a shorter geographical distance to an air sampler. A similar observation regarding distance was made in a study carried out at Hamerton Zoo Park, UK, where airborne eDNA was found to be concentrated around areas recently inhabited by zoo animals.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The 49 detected species included zoo animals, locally occurring animals, and animals used as feed at the zoo. The ability to detect this range of vertebrates through airborne eDNA is supported by Clare et al 19 We found an increased probability of detecting airborne eDNA from animals present in high biomass and within a shorter geographical distance to an air sampler. A similar observation regarding distance was made in a study carried out at Hamerton Zoo Park, UK, where airborne eDNA was found to be concentrated around areas recently inhabited by zoo animals.…”
Section: Discussionsupporting
confidence: 66%
“…The ability to detect this range of vertebrates through airborne eDNA is supported by Clare et al. 19 …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, capture-based surveys are central to understanding the role bats could play in epidemiology (Streicker and Gilbert 2020 ). Furthermore, many cryptic bat species are difficult to identify conclusively whether in a photograph or in the hand, and may require molecular methods for confident identification (e.g., Francis et al 2010 ; Clare et al 2011 ), although novel approaches may allow collection of DNA material such as from air in a roost without handling bats (Clare et al 2022 ). Neither acoustic nor photographic surveys alone can provide reliable information on population sizes or demographics, which may require additional methods such as mark-recapture studies.…”
Section: Discussionmentioning
confidence: 99%